Crop productivity, yield and seasonality of breadfruit (Artocarpus spp., Moraceae). (12th September 2014) - Liu, Ying; P. Jones, A. Maxwell; J. Murch, Susan; Ragone, Diane
Abstract : Introduction . Breadfruit, Artocarpus spp., is a staple crop with the potential to alleviate hunger and increase food security in tropical regions. Guidelines and recommendations for cultivar selection and production practices are now required for establishment of breadfruit in new areas.Materials and methods . To respond to this need for spreading breadfruit, our study quantified the growth, development, yield and seasonality of 24 breadfruit cultivars (26 trees) established in Kauai, Hawaii, over a 7-year period from 2006–2012. Individual production profiles were generated for each accessioned cultivar based on major agricultural factors.Results . Across all cultivars of breadfruit ( A. altilis ), an average of 269 fruits per year was produced by each tree with an average fruit weight of 1.2 kg. Based on the planting density of 50 trees×ha–1, this translates to an average projected yield of 5.23 t×ha–1 after 7 years. Hybrids ( A. altilis × A. mariannensis ) had a higher yield than breadfruit. The data of our article support the previously proposed hypothesis for predicting breadfruit seasonality. On average, the peak season occurred from July to November.Conclusions . Ma'afala, the first widely available commercial cultivar, started to bear fruit within 22 to 23 months of planting. Other cultivars with potential for commercial production include Toneno, White, Rotuma and Meinpadahk.